Updated List of Bryophytes from Cape Verde Archipelago - Sim-Sim, Maria (2024)
The aim of the present study is to update the list of bryophytes in the Cape Verde archipelago, with a focus on its distinctive terrestrial biota. The research was carried out through a combination of herbarium collections revision and fieldwork conducted from 2016 to 2019. The revised list includes 185 bryophyte taxa (175 species, 5 subspecies, and 5 varieties) from 93 genera and 42 families. Notably, 8 taxa are endemic, and the inclusion of 35 new taxa further enriches the bryophyte diversity of the archipelago. The distribution of bryophyte taxa varies across islands, with Santo Antão, São Nicolau, and Fogo exhibiting particularly high diversity. Acrocarpous mosses are the most common growth form (58.4%), followed by pleurocarpous mosses, thalloid liverworts (15.1% each), and leafy liverworts (11.4%). In conclusion, this study provides valuable insights into the bryophyte diversity of southern Macaronesia enhancing our understanding of its unique flora and emphasizing the imperative need for conservation efforts.